Role of exogenous folic acid in alleviation of morphological and anatomical inhibition on salinity-induced stress in barley - Kilic, Semra; Aca, Hatice TuÄŸba (Italian Journal of Agronomy, 2016)
Soil salinity is a serious threat to agricultural ecological environment and agriculture sustainability. Ever increasing salinity negatively affects processes such as plant growth and development, ultimately causing diminished economic yield and quality of production, and it might cause a worldwide famine in the future. Thus, helping plants adapt to saline soils and increasing their yield and quality is a must. Our study focused on the enhancing role of exogenously applied folic acid (FA) in mitigation of toxicity caused by salt (NaCl). Barley seeds were pre-treated with 50 ÂµM FA for 24 h and then exposed to salt. Morphological and anatomical changes in seed germination and seedling growth stages were compared between different treatments of salt in laboratory conditions. Adverse effects of salt in both germination and seedling growth stages depended on the concentration of salt treatment (0.0, 0.25, 0.275, 0.30, 0.325 and 0.35 M). It was shown that the application of FA effectively alleviated the salt-induced inhibition, and reduced the negative effects of salt on germination (germination index and vigour index), seedling growth (radicle and coleoptile lengths, fresh weight) and leaf (stomata and epidermis number, stomatal index, stomata sizes of adaxial and abaxial surfaces) parameters. Moreover, FA elevated all examined parameters of barley also under non-stress conditions. Especially, germination and vigour indices were significantly higher than the control. Our results suggest that exogenous FA is involved in the resistance of barley to salt-stress.